1973
DOI: 10.1007/bf01882332
|View full text |Cite
|
Sign up to set email alerts
|

Head injuries caused by small-calibre, high velocity bullets

Abstract: The effect of firearm calibre and bullet velocity on head wounds were studied in anaesthetized dogs. Autopsy, radiological and microscopic studies were undertaken. It was found that the injuries inflicted by 7.62 mm ammunition with an impact velocity of 714--798 m/see were generally less severe than those inflicted by 5.56 mm ammunition with an impact velocity of 810 to approx. 1000 m/sec.Effects of low velocity were observed when the 7.62 mm ammunition was used. Typical high velocity effects were noted with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Although multiple gunshots cause an extensive and sometimes very complex pattern of fractures (hydrodynamic effect produced by the bullet transversing the temporal cavity of the brain) [5][6][7][8], in the majority of cases Puppe's rule can be successfully applied [3,4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Although multiple gunshots cause an extensive and sometimes very complex pattern of fractures (hydrodynamic effect produced by the bullet transversing the temporal cavity of the brain) [5][6][7][8], in the majority of cases Puppe's rule can be successfully applied [3,4,[9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In a simple experimental model for tangential wounds, the peak pressure was approximately dependent on the square of the projectile's velocity but not on the mass (Clemedson et al 1973). The results of pressure measurements by Dittmann (1989) and Watkins et al (1988), however, showed that projectile mass is also important in nontangential trajectories at least.…”
Section: Special Wound Ballistics Of the Headmentioning
confidence: 90%
“…Because of the inelastic quality and the high water content of brain tissue, it is per se very vulnerable to cavitation and stretch mechanism (Fackler 1991). The penetration of the skull can imply the generation of secondary missiles in the form of bone or bullet fragments (Clemedson et al 1973;Kirkpatrick and DiMaio 1978;Allen et al 1983;Finnie 1993) and a tendency towards early tumling or deformation of the bullet. Kirkpatrick and DiMaio (1978), for example, were able to demonstrate intracerebral bone chips solely by digital palpation of the brain in 16 out of 42 cases of civilian gunshot wounds to the brain.…”
Section: Special Wound Ballistics Of the Headmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Versuche sind auch von Interesse, welt sie unter anderem Hochgeschwindigkeitsgeschosse betreffen, tiber deren Verletzungswirkung am Sch~idel nur wenig Material vorliegt [4]. Wir wollen die aufgrund unserer Untersuchungen erschlossenen Hypothesen darlegen, wobei wir aus Grtinden des grundsfitzlich anderen Ablaufes zwei Ffille unterscheiden und getrennt diskutieren mtissen: Den einen Fall, bei dem der Helm durchschossen wird und das Geschol3 in den Kopf eindringt, und den anderen Fall, dab der Helm dem Beschug standh~ilt.…”
Section: Diskussionunclassified